Pendidikan Agama Berbasis Kerukunan - Roibin, Roibin (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2003)
The Islamic education has ever been sociologically and historically regarded as Islamic religious education. It is intended to differentiate it from general (secular) education. This view is considered as the reason for the presence of Islamic religious school (madrasah diniyah) and the dichotomy between religious education and general (secular) education. Since then, the treatment for students'. characters, moral, attitude, personality or what commonly known as affective aspects is relied on religious education. On the contrary, the treatment for students 'psychometrics and cognitive aspects is charged to general education system.